A guide to musical styles : from madrigal to modern music - Moore, Douglas, 1893-1969. (New York, N.Y. : W.W. Norton & Co., 1962)
This book transports the reader into the spirit of great music, so that when he encounters an unfamiliar composition he will feel at home in its style and will have some idea of what to expect. It examines five great periods-the Renaissance, Baroque, Classic, Romantic, and Modern-and teaches him the technique of listening so that he can identify the style and form of a piece of music and place it in its proper period. For unless our ears can tell us the difference between a fugue and a sonata, the study of names, dates and historical trends will be futile.
The renaissance -- The baroque -- The classic era -- The romantic era -- The post-romantic and modern periods.
Includes bibliographical references (p.[337]-340), index, and dictionary of musical terms.
Keywords: Musical form; Music -- History